High-grade resin lead core manufactured based on magnetic material and manufacturing method
Through the mixing of thermosetting resin and thermoplastic resin and modification of magnetic particles, the problems of easy aggregation of magnetic particles in the lead core of resin are solved, and a high-level resin lead core with excellent writing smoothness and mechanical properties are prepared.
Patent Information
- Application Number
- CN202411414028.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
AI Technical Summary
Magnetic particles in the lead resin easily aggregate and affect writing, and have poor mechanical properties, making it difficult to use effectively in high-end occasions.
A high-level resin lead core with excellent mechanical properties is prepared by mixing thermosetting resin and thermoplastic resin, combined with magnetic particles modification and modification, through specific process flows such as stirring, ultrasonication, rolling and extrusion.
It improves the writing smoothness and mechanical properties of lead core, reduces the risk of magnetic particles falling off, and enhances the flexural strength and clarity of writing traces.
Smart Images

Figure CN119220128A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of resin lead core manufacturing, and in particular to a high-grade resin lead core manufactured based on magnetic materials and a manufacturing method. Background Art
[0002] Compared with the traditional graphite and clay composite lead, resin lead has the characteristics of thin core, easy processing, smooth writing and clear handwriting, and is currently the most popular lead product. For some high-end occasions, users require the lead to have both clear writing marks and high flexural strength. However, to improve the clarity of the lead's writing marks, more graphite needs to be added, and the lead with more graphite is often soft and brittle, and it is easy to break when the lead is subjected to a small force, thereby reducing the writing comfort.
[0003] Magnetic particles are very easy to aggregate due to their own magnetism, which makes it difficult for the lead to write smoothly and to give full play to its excellent performance. Some researchers have loaded magnetic particles onto the surface of graphite to obtain resin lead with better writing comfort. However, due to the easy aggregation of magnetic particles and the weak interaction between magnetic particles and graphite surface, magnetic particles are easy to fall off from graphite, and this kind of lead has poor mechanical properties such as bending strength and impact strength. Summary of the invention
[0004] The present application provides a high-grade resin lead core manufactured based on magnetic materials and a manufacturing method, so as to solve the technical problems in the prior art that magnetic particles in the resin lead core are easy to aggregate and affect writing, and the lead core has poor mechanical properties.
[0005] In a first aspect, the present application provides a method for manufacturing a high-grade resin lead based on a magnetic material, the method comprising:
[0006] Adding thermosetting resin and thermosetting resin into the solvent, stirring with a high-speed stirrer to dissolve them, and obtaining a first mixed solution;
[0007] Adding a colorant, magnetic particles and a plasticizer into a solvent, stirring rapidly, placing the mixture in an environment below zero degrees Celsius for 1 to 10 hours, taking the mixture out, heating it to 90 to 95 degrees Celsius, and cooling it to room temperature to obtain a second mixed solution;
[0008] The second mixed liquid is added to the first mixed liquid, and the solvent is evaporated by stirring at room temperature to 150° C., and the water is expelled by rolling with a three-roll mill, and the lead bars are extruded with an extruder.
[0009] In a possible implementation manner, the thermosetting resin is selected from: any one of furan resin, phenolic resin, epoxy resin, β resin or polyimide;
[0010] The thermoplastic resin is selected from any one of polyvinyl alcohol (PVA), low-temperature polyethylene, ethylene-vinyl acetate copolymer (EVOH) or polyoxymethylene.
[0011] In a possible implementation manner, the magnetic particles include: any one of iron powder, nickel powder, cobalt powder, iron oxide powder, cobalt oxide powder or nickel oxide powder;
[0012] The particle size of the magnetic particles is 50 to 400 nm;
[0013] The solvent is selected from any one or more of tetrahydrofuran, N,N-dimethylformamide or N,N-dimethylacetamide.
[0014] In one possible implementation, the colorant is selected from any one of flake graphite, artificial graphite, carbon black or boron nitride;
[0015] The plasticizer is selected from any one of dioctyl phthalate, polyethylene glycol, an emulsifier, a dispersant, and a stabilizer.
[0016] In a possible implementation manner, the mass ratio of the thermosetting resin, the thermosetting resin, the colorant, the magnetic particles and the plasticizer is (0.5-0.8): (2.5-3.5): (3.8-5): (0.2-0.5): (0.1-0.35);
[0017] Talcum powder is also added to the second mixed liquid, and the mass ratio of the talcum powder to the colorant is 0.1-0.5:1.
[0018] In a possible implementation manner, before adding the colorant, magnetic particles and plasticizer to water and ethanol and rapidly stirring, the method further comprises:
[0019] The colorant is added to a ball mill for grinding, added to a mixed solution of ethanol and water for ultrasonication for 0.2 to 1 h, and magnetic particles are added for continuous ultrasonication for 0.1 to 0.5 h;
[0020] Add acrylamide monomer and N,N-methylenebisacrylamide to the above mixed solution, place at 2-5°C for 10 minutes, add potassium persulfate and tetramethylethylenediamine, stir and place at -12--10°C for 10-12 hours, wash and dry;
[0021] The amount of the acrylamide monomer is 2-5% of the colorant, and the amount of the tetramethylethylenediamine is 0.1-0.3% of the colorant. In a possible implementation, after the lead strip is extruded using a three-roll mill, the method further includes:
[0022] Cut the lead bar into equal lengths, place the lead bar at 100-130° C. and dry it for 1-6 hours, then heat it to 150-180° C. and dry it for 8-15 hours to obtain an intermediate lead core;
[0023] The intermediate lead core is placed in an electric furnace, and the temperature is raised from room temperature to 1000-1200°C, and the temperature is kept constant at 0.5-2°C, and after being taken out and cooled, it is immersed in liquid white oil for 1-4 hours to obtain a lead core; wherein the program heating rate is 1.5-2.2°C / min;
[0024] The lead strip has a diameter of 0.3 to 2.0 mm, including but not limited to 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm or 2.0 mm.
[0025] In a second aspect, the present application provides an advanced resin lead core manufactured based on magnetic materials, wherein the resin lead core is manufactured by the manufacturing method described in any one of the embodiments of the first aspect.
[0026] The present application provides a method for manufacturing a high-grade resin lead based on magnetic materials, which has the following beneficial effects:
[0027] 1. In the present application, the colorant and magnetic particles are modified and modified, which can reduce the agglomeration of the colorant to a certain extent, so that the colorant and the magnetic particles have a higher bonding effect, and the magnetic particles are not easy to fall off the graphite, so that the lead core can be written on the magnetic plate with excellent writing marks.
[0028] 2. In the present application, a thermosetting resin and a thermosetting resin are mixed in a certain proportion as the lead core material, which can well enhance the mechanical properties of the lead core. Compared with the lead core using only one resin, its mechanical properties are relatively excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0030] Figure 1 A process flow of manufacturing a high-grade resin lead based on magnetic materials provided in the embodiment of the present application Figure 1 ;
[0031] Figure 2 A process flow of manufacturing a high-grade resin lead based on magnetic materials provided in the embodiment of the present application Figure 2 .
[0032] The above-mentioned drawings have shown specific embodiments of the present application, which will be described in more detail below.
[0033] These drawings and textual descriptions are not intended to limit the scope of the present application in any way, but rather to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0034] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application. Instead, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.
[0035] The technical solution of the present application and how the technical solution of the present application solves the above-mentioned technical problems are described in detail below with specific embodiments. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments. The embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0036] Embodiment 1:
[0037] A method for manufacturing a high-grade resin lead based on magnetic materials, comprising:
[0038] S301, adding furan resin and ethylene-vinyl acetate copolymer (EVOH) into tetrahydrofuran and N,N-dimethylformamide in a ratio of 1:1, stirring with a high-speed stirrer to dissolve, and obtaining a first mixed solution.
[0039] S302, adding flake graphite into a ball mill for grinding, adding into a mixed solution of ethanol and water for ultrasonication for 1 hour, and adding magnetic particles for further ultrasonication for 0.5 hour.
[0040] S303, adding acrylamide monomer and N,N-methylenebisacrylamide to the above-mentioned mixed solution, placing it at 5°C for 10 minutes, adding potassium persulfate and tetramethylethylenediamine, stirring and placing it at -12°C for 10 hours, washing and drying; wherein the amount of acrylamide monomer is 2% of the colorant, and the amount of tetramethylethylenediamine is 0.15% of the colorant.
[0041] S304, adding flake graphite, iron powder and polyethylene glycol to the solvent, stirring rapidly, placing at -5°C for 10 hours, taking out and heating to 95°C, cooling to room temperature to obtain a second mixed solution. S305, adding the second mixed solution to the first mixed solution, stirring at 150°C to evaporate the solvent, using a three-roll mill to roll out water, and using an extruder to extrude lead bars.
[0042] S306. Cut the lead bar into equal lengths, place them at 130°C and dry them for 6 hours, then program the temperature to 160°C and dry them for 8 hours to obtain an intermediate lead core; place the intermediate lead core in an electric furnace, program the temperature from room temperature to 1000°C, and keep the temperature constant for 1 hour, take them out and cool them, then immerse them in liquid white oil for 2 hours and take them out to obtain the lead core; wherein the program temperature increase rate is 1.5°C / min.
[0043] After testing, the diameter of the lead core is 0.55mm, its flexural strength is 420MPa, its writing lubricity is excellent and the writing mark color is 27.7.
[0044] Embodiment 2:
[0045] A method for manufacturing a high-grade resin lead based on magnetic materials, comprising:
[0046] S301, adding furan resin and ethylene-vinyl acetate copolymer (EVOH) into tetrahydrofuran and N,N-dimethylformamide in a ratio of 1:1, stirring with a high-speed stirrer to dissolve, and obtaining a first mixed solution.
[0047] S302, adding artificial graphite into a ball mill for grinding, adding it into a mixed solution of ethanol and water for ultrasonication for 0.5 h, and adding magnetic particles for further ultrasonication for 0.2 h.
[0048] S303, adding acrylamide monomer and N,N-methylenebisacrylamide to the above-mentioned mixed solution, placing it at 5°C for 10 minutes, adding potassium persulfate and tetramethylethylenediamine, stirring and placing it at -12°C for 12 hours, washing and drying; wherein the amount of acrylamide monomer is 2% of the colorant, and the amount of tetramethylethylenediamine is 0.15% of the colorant.
[0049] S304, adding artificial graphite, cobalt powder and polyethylene glycol into the solvent, stirring rapidly, placing at -5°C for 5 hours, taking out, heating to 90°C, and cooling to room temperature to obtain a second mixed solution.
[0050] S305, adding the second mixed solution to the first mixed solution, stirring at 150°C to evaporate the solvent, using a three-roll mill to roll out the water, and using an extruder to extrude the lead bars.
[0051] S306. Cut the lead bar into equal length segments, place them at 120°C to dry for 5 hours, program the temperature to 150°C for 20 hours, and then dry them for 10 hours to obtain an intermediate lead core; place the intermediate lead core in an electric furnace, program the temperature from room temperature to 1200°C, and keep the temperature constant for 1 hour, take it out and cool it, then immerse it in liquid white oil for 3 hours to obtain the lead core; wherein the program temperature increase rate is 2°C / min.
[0052] After testing, the diameter of the lead core is 0.56mm, its flexural strength is 399MPa, its writing lubricity is excellent and the writing mark color is 26.4.
[0053] Embodiment 3:
[0054] A method for manufacturing a high-grade resin lead based on magnetic materials, comprising:
[0055] S301, adding furan resin and polyvinyl alcohol (PVA) to tetrahydrofuran and N,N-dimethylformamide in a ratio of 1:1, stirring with a high-speed stirrer to dissolve, and obtaining a first mixed solution.
[0056] S302, adding carbon black into a ball mill for grinding, adding into a mixed solution of ethanol and water for ultrasonication for 1 hour, and adding magnetic particles for further ultrasonication for 0.5 hour.
[0057] S303, adding acrylamide monomer and N,N-methylenebisacrylamide to the above-mentioned mixed solution, placing it at 2°C for 10 minutes, adding potassium persulfate and tetramethylethylenediamine, stirring and placing it at -11°C for 10 hours, washing and drying; wherein the amount of acrylamide monomer is 2% of the colorant, and the amount of tetramethylethylenediamine is 0.15% of the colorant.
[0058] S304, adding carbon black, nickel powder and dioctyl phthalate into the solvent, stirring rapidly, placing at -5°C for 8 hours, taking out, heating to 92°C, and cooling to room temperature to obtain a second mixed solution.
[0059] S305, adding the second mixed solution to the first mixed solution, stirring at 120°C to evaporate the solvent, using a three-roll mill to roll out the water, and using an extruder to extrude the lead bars.
[0060] S306. Cut the lead bar into equal length segments, place them at 120°C to dry for 4 hours, program the temperature to 150°C for 10 hours, and then dry them for 12 hours to obtain an intermediate lead core; place the intermediate lead core in an electric furnace, program the temperature from room temperature to 1000°C, and keep the temperature constant for 1.5 hours, take it out and cool it, then immerse it in liquid white oil for 3 hours to obtain the lead core; wherein the program temperature increase rate is 1.5°C / min.
[0061] After testing, the diameter of the lead core is 0.55mm, its flexural strength is 411MPa, its writing lubricity is excellent and the writing mark color is 26.8.
[0062] Comparative Example 1:
[0063] The only difference between this comparative example and Example 1 is that this comparative example does not contain steps S302 and S303.
[0064] After testing, the diameter of the lead core is 0.55mm, its flexural strength is 388MPa, its writing lubricity is excellent and the writing mark color is 16.4.
[0065] Comparative Example 2:
[0066] The difference between this comparative example and Example 1 is that this comparative example does not contain steps S302 and S303, and contains only ethylene-vinyl acetate copolymer (EVOH). After testing, the diameter of the lead is 0.56 mm, its flexural strength is 245 MPa, the writing lubricity is excellent, and the writing trace chromaticity is 15.8.
[0067] Comparative Example 3:
[0068] The difference between this comparative example and Example 1 is that this comparative example does not contain steps S302 and S303, and contains only furan resin.
[0069] After testing, the diameter of the lead core is 0.55mm, its flexural strength is 266MPa, its writing lubricity is excellent and the writing mark color is 16.2.
[0070] Specifically, in the above specific embodiments of the present invention, the flexural strength is tested by a HY-307B flexural strength tester, and the writing lubricity and writing trace chromaticity are in accordance with the GB / T26698-2011 standard. In summary, the present invention provides a method for manufacturing a high-grade resin lead based on magnetic materials, the lead is smooth to write, the lead formula raw material cost is low, and industrial production can be achieved without changing the traditional process.
[0071] Unless otherwise indicated, the terms and phrases used herein have the meanings listed below. A particular term or phrase should not be considered to be indefinite or unclear unless otherwise defined, but should be interpreted according to the meaning generally understood by those skilled in the art. When a trade name appears in this article, it is intended to refer to the corresponding commercial product or its active ingredient.
[0072] Unless otherwise specifically defined or reasonably judged from the context, the ratios (including percentages) or parts used herein are all by weight. The terms "about" and "approximately" when used with numerical variables generally refer to the numerical value of the variable and all numerical values of the variable within experimental error (e.g., within a 95% confidence interval for the mean value) or within ±10% of the specified numerical value, or within a wider range.
[0073] The expression "comprising" or its synonymous similar expressions "including", "containing" and "having" etc. are open-ended and do not exclude additional unrecited elements, steps or ingredients. The expression "consisting of excludes any element, step or ingredient not specified. The expression "consisting essentially of means that the scope is limited to the specified elements, steps or ingredients, plus the optional elements, steps or ingredients that do not materially affect the basic and novel characteristics of the claimed subject matter. It should be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".
[0074] The term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes both occurring and not occurring of said event or circumstance.
[0075] The expression "one or more" or "at least one" may mean 1, 2, 3, 4, 5, 6, 7, 8, 9 or more.
[0076] The term "and / or" encompasses "and" and "or". Elements qualified by "and / or" are intended to encompass any one of them and any combination thereof. For example, A and / or B encompasses A, B, and A+B. A, B, and / or C encompasses A, B, C, A+B, A+C, B+C, and A+B+C. Other embodiments of the present application will readily occur to those skilled in the art after considering the specification and practicing the invention disclosed herein.
[0077] This application is intended to cover any variation, use or adaptation of the present application, which follows the general principles of the present application and includes common knowledge or customary technical means in the art that are not disclosed in the present application. The description and examples are to be regarded as exemplary only, and the true scope and spirit of the present application are indicated by the following claims.
[0078] It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. A method for manufacturing a high-grade resin lead based on magnetic materials, characterized in that: The method comprises: Adding thermosetting resin and thermosetting resin to a solvent, stirring with a high-speed stirrer to dissolve, to obtain a first mixed solution; adding a colorant, magnetic particles and a plasticizer to the solvent, stirring rapidly, placing in an environment below zero degrees Celsius for 1 to 10 hours, taking out, heating to 90 to 95 degrees Celsius, and cooling to room temperature to obtain a second mixed solution; The second mixed liquid is added to the first mixed liquid, and the solvent is evaporated by stirring at room temperature to 150° C., and the water is expelled by rolling with a three-roll mill, and the lead bars are extruded with an extruder.
2. The method according to claim 1, characterized in that: The thermosetting resin is selected from any one of furan resin, phenolic resin, epoxy resin, β resin or polyimide; The thermoplastic resin is selected from: polyvinyl alcohol (PVA), low-temperature polyethylene, ethylene-vinyl acetate Any of copolymer (EVOH) or polyoxymethylene.
3. The method according to claim 1, characterized in that: The magnetic particles include any one of iron powder, nickel powder, cobalt powder, iron oxide powder, cobalt oxide powder or nickel oxide powder; The particle size of the magnetic particles is 50 to 400 nm; The solvent is selected from any one or more of tetrahydrofuran, N,N-dimethylformamide or N,N-dimethylacetamide.
4. The method according to claim 1, characterized in that: The colorant is selected from any one of flake graphite, artificial graphite, carbon black or boron nitride; The plasticizer is selected from any one of dioctyl phthalate, polyethylene glycol, an emulsifier, a dispersant, and a stabilizer.
5. The method according to claim 1, characterized in that: The mass ratio of the thermosetting resin, the thermosetting resin, the colorant, the magnetic particles and the plasticizer is (0.5-0.8): (2.5-3.5): (3.8~5):(0.2~0.5):(0.1~0.35); Talcum powder is also added to the second mixed liquid, and the mass ratio of the talcum powder to the colorant is 0.1-0.5:
1.
6. The method according to claim 1, characterized in that: Before the colorant, magnetic particles and plasticizer are added to water and ethanol and rapidly stirred, the process further includes: adding the colorant to a ball mill for grinding, adding the colorant to a mixed solution of ethanol and water for ultrasonication for 0.2 to 1 hour, and adding the magnetic particles for continuous ultrasonication for 0.1 to 0.5 hour; Add acrylamide monomer and N,N-methylenebisacrylamide to the above mixed solution, place at 2-5°C for 10 minutes, add potassium persulfate and tetramethylethylenediamine, stir and place at -12--10°C for 10-12 hours, wash and dry; The amount of the acrylamide monomer used is 2-5% of the colorant, and the amount of the tetramethylethylenediamine used is 0.1-0.3% of the colorant.
7. The manufacturing method according to claim 1, characterized in that: After the lead strip is extruded by the three-roller mill, the method further comprises: Cut the lead bar into equal lengths, place the lead bar at 100-130° C. and dry it for 1-6 hours, then heat it to 150-180° C. and dry it for 8-15 hours to obtain an intermediate lead core; The intermediate lead core is placed in an electric furnace, and the temperature is raised from room temperature to 1000-1200°C, and the temperature is kept constant for 0.5-2h, and after being taken out and cooled, it is immersed in liquid white oil for 1-4h to obtain a lead core; wherein the program heating rate is 1.5-2.2°C / min; The lead strip has a diameter of 0.3 to 2.0 mm, including but not limited to 0.3 mm, 0.5 mm, 0.7 mm, 0.9 mm, 1.3 mm or 2.0 mm.
8. A high-grade resin lead made of magnetic material, characterized in that: The resin lead is manufactured by the manufacturing method according to any one of claims 1 to 7.